The Political Economy of Sanitation : How Can We Increase Investment and Improve Service for the Poor? - World Bank (Washington, DC, 2014)
This study follows current approaches to political economy-interdisciplinary inquiry drawing upon social and political theory and economic principles-to understand how political actors, institutions, and economic processes influence each other. The 'political economy of sanitation,' therefore, refers to the social, political, and economic processes and factors that determine the extent and nature of sanitation investment and service provision. This study's conceptual framework combines a diagnostic component with a typology of actions to help translate analytical findings into more effective support to operations and investments. The diagnostic framework aims to identify political economy constraints as well as opportunities that are entry points for subsequent operational actions. The study was conducted through a qualitative analysis of stakeholders, institutions, impacts, risks, and opportunities that was linked to processes and policy debate. This synthesis report is based on the findings from the secondary literature review and the results of primary research in the four case study countries, which examined how each had identified and managed political economy risks and opportunities in its sanitation interventions. Overall, the study confirms the importance of assessing stakeholder interests, identifying potential winners and losers, identifying incentives, and examining formal and informal institutions.